2016
DOI: 10.1161/jaha.115.003122
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of the Voltage‐Gated K + Channel β2 Subunit in a Familial Case of Brugada Syndrome

Abstract: BackgroundThe Brugada syndrome is an inherited cardiac arrhythmia associated with high risk of sudden death. Although 20% of patients with Brugada syndrome carry mutations in SCN5A, the molecular mechanisms underlying this condition are still largely unknown.Methods and ResultsWe combined whole‐exome sequencing and linkage analysis to identify the genetic variant likely causing Brugada syndrome in a pedigree for which SCN5A mutations had been excluded. This approach identified 6 genetic variants cosegregating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…In human, I to is generated by the K V 4.3 channel, which is encoded by the gene KCND3 (Niwa and Nerbonne, 2010 ). Gain-of-function mutations in KCND3 , or its regulatory subunits, have also been associated with BrS (Delpón et al, 2008 ; You et al, 2015 ; Portero et al, 2016 ), giving rise to an ongoing discussion on the apparent role of I to in the pro-arrhythmic mechanism of BrS (Wilde et al, 2010 ). Previous studies have suggested that an increased I to may directly affect cardiac conduction due to a current-to-load mismatch during the depolarization process (Hoogendijk et al, 2010a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…In human, I to is generated by the K V 4.3 channel, which is encoded by the gene KCND3 (Niwa and Nerbonne, 2010 ). Gain-of-function mutations in KCND3 , or its regulatory subunits, have also been associated with BrS (Delpón et al, 2008 ; You et al, 2015 ; Portero et al, 2016 ), giving rise to an ongoing discussion on the apparent role of I to in the pro-arrhythmic mechanism of BrS (Wilde et al, 2010 ). Previous studies have suggested that an increased I to may directly affect cardiac conduction due to a current-to-load mismatch during the depolarization process (Hoogendijk et al, 2010a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Gene test of SCN5A may not be sufficient as mutations in about 20 other genes have already been identified in patient with BrS. [ 13 ] So, it is too early to totally rule out BrS. Irrespective, whether a pattern of BrS-like ECG may bring a warning sign for life-threatening ventricular arrhythmias, and the prognosis of our patient still needs to be followed up further.…”
Section: Discussionmentioning
confidence: 97%
“…[ 12 ] Accelerated inactivation of sodium channels and predominance of transient outward potassium current creates a gradient of the action potential in different layers of RVOT at the beginning of repolarization, imbalanced endocardial and epicardial action potentials explain the underlying mechanism of BrS. [ 1 ] Transient ischemia of large area affects the activities of inactivation particles, which promote changes in sodium channel structure and instability of the inactivated state of the channel. [ 12 ] Different inactivated states of sodium channel lead to different amplitude of transient outward potassium, which could explain the Brugada-like ST elevation and alternans of ST-T waves in the ECG (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include KCNE3, KCND3, and SEMA3A (semaphorin, an endogenous K + channel inhibitor) responsible for I to (Delpón et al, 2008 ; Giudicessi et al, 2011 , 2012 ; Ohno et al, 2011 ; Nakajima et al, 2012 ; Boczek et al, 2014 ), KCNJ8 and ABCC9 (encoding for SUR2A, the ATP-binding cassette transporter for the K ATP channel) determining I K, ATP (Medeiros-Domingo et al, 2010 ; Hu et al, 2014b ) and KCNH2 encoding for I Kr (Wang et al, 2014 ). Most recently, dysfunction in the KCNAB2, which encodes the voltage-gated K + channel β2-subunit, was associated with increased I to activity and identified as a putative gene involved in BrS (Portero et al, 2016 ). Finally, loss-of-function mutations in HCN4 leading to decreased I f and gain- or loss-of-function mutations in the transient receptor potential melastatin protein 4 gene (TRPM4) have also been implicated in BrS (Ueda et al, 2009 ; Liu et al, 2013 ).…”
Section: Electrophysiological Mechanisms Underlying Arrhythmogenesis mentioning
confidence: 99%